SHINEⓇ: modelo para la transformación de espacios educativos - Teba-Fernández, Eva María; Caballero-García, Presentación; Bueno-Villaverde, Ángeles (Journal of Learning Styles, 2020)
When undertaking reforms or transformations in an educational environment, Headmasters and Management Teams must make decisions that will lead to a significant economic investment, without previously having a clear evidence on the impact that this transformation will have on their stakeholders (students, families, teachers and non-teaching staff). The authors have used a methodology of documentary analysis, consulted databases of academic and scientific rigor and reviewed the existing literature of the last 24 years, in Spanish and English, on the impact of educational spaces on the people who use them and their behaviors. They thus offer a pentadimensional guide-model for the building or transformation of school spaces, SHINE®, a theoretically based model that holistically integrates those dimensions that help align this innovative spatial transformation with the Educational Project and the Organization Strategic Plan. The dimensions are Stimulation; Human Centered; Individualization; Naturalness and Environmentally Friendly. The results are discussed related to the need to promote these educational changes and their evaluation, in order to determine their personal, educational and social impact.